Language and Colonialism: A Historical Study on the Development of Dutch Loanwords in Indonesian - Safinatul Hasanah Harahap; Desta Riani Br Perangin-angin; Jesika Indah Sari Purba; Santa Hoky Br Sembiring; Desveromonika Zalukhu (Warisan: Journal of History and Cultural Heritage, 2025)
This study investigates the historical development of Dutch loanwords in the Indonesian language, situating it within the broader context of colonialism and linguistic transformation. The study is premised on the assumption that colonial rule not only shaped political and economic structures but also left a profound impact on language. The central research question investigates how Dutch colonialism contributed to the development and integration of Dutch-derived vocabulary in Indonesian. Employing a historical-linguistic methodology, this study combines etymological analysis with archival and textual sources from the colonial period to trace the semantic evolution and socio-political function of selected loanwords. The findings reveal that Dutch loanwords are predominantly found in administrative, legal, educational, and technological domains, reflecting the sectors most influenced by colonial governance. These borrowings did not merely enrich the lexicon but also signified a shift in epistemic frameworks during the colonial encounter. The article argues that the linguistic legacy of colonialism in Indonesia is not a passive imprint but an active site of negotiation and adaptation. This study contributes to a deeper understanding of the entangled relationship between language and power in postcolonial societies and highlights the importance of historical inquiry in linguistic research.